Fallow and Sesbania Effects on Soil Nitrogen Dynamics in Lowland Rice-Based Cropping Systems - Buresh, R.J.; Chua, T.T.; Castillo, E.G.; Liboon, S.P.; Garrity, D.P. (Wiley, 1993)
Vast areas of rice‐growing (Oryza sativa L.) lowlands in Asia are fallowed or cropped with non‐rice crops for part of the year. Nitrate can accumulate during the fallow or non‐rice crop, but this nitrate can be lost upon flooding for rice production. To determine fallow and green manure crop effects on soil nitrate and ammonium dynamics in lowland riceland, a 2‐yr field study was conducted in the Philippines. Treatments before wet season rice were (i) Sesbania rostrata grown for either 45 or 60 d, (ii) weedy fallow, and (iii) weed‐free fallow. Sesbania rostrata was sown with irrigation in late April‐early May, rains started in early (1989) or mid‐May (1990). Weeds and S. rostrata were incorporated after soil flooding on 23 June. Rains increased soil water‐filled pore space to above 0.75 mL mL−1 between mid‐May and soil flooding. Weeds and S. rostrata assimilated soil nitrate, as evidenced by lower (P < 0.05) nitrate in those treatments than in the weed‐free fallow. The decrease in soil nitrate in the weedfree fallow from 24 April to before soil flooding (15 kg N ha−1) was apparently due to denitrification or leaching; additional nitrate (19 kg N ha−1 in 1990) disappeared after soil flooding. Ammonium‐N was rapidly released from incorporated weeds and S. rostrata. It reached a maximum by 36 d after incorporation, which correlated (r = 0.95) with N accumulation by rice at 45 d after transplanting. Results suggest that weeds and crops before rice can reduce soil N loss by assimilating nitrate‐N and then cycling this N through incorporated plant residues back to the soil where it is rapidly mineralized and used by rice.